Sobre a convergência de métodos de descida em otimização não-suave: aplicações à ciência comportamental - Sousa Júnior, Valdinês Leite de (2017)
In this work, we investigate four different types of descent methods: a dual descent method in the scalar context and a multiobjective proximal point methods (one exact and two inexact versions). The first one is restricted to functions that satisfy the Kurdyka-Lojasiewicz property, where it is used a quasi-distance as a regularization function. In the next three methods, the objective is to study the convergence of a multiobjective proximal methods (exact an inexact) for a particular class of multiobjective functions that are not necessarily differentiable. For the inexact methods, we choose a proximal distance as the regularization term. Such a well-known distance allows us to analyze the convergence of the method under various settings. Applications in behavioral sciences are analyzed in the sense of the variational rationality approach.